ErbB4 Activated p38γ MAPK Isoform Mediates Early Cardiogenesis Through NKx2.5 in Human Pluripotent Stem Cells. (15th October 2015) - Ramachandra, Chrishan J.A.; Mehta, Ashish; Wong, Philip; Shim, Winston
Abstract: Activation of ErbB4 receptor signaling is instrumental in heart development, lack of which results in embryonic lethality. However, mechanism governing its intracellular signaling remains elusive. Using human pluripotent stem cells, we show that ErbB4 is critical for cardiogenesis whereby its genetic knockdown results in loss of cardiomyocytes. Phospho-proteome profiling and Western blot studies attribute this loss to inactivation of p38γ MAPK isoform which physically interacts with NKx2.5 and GATA4 transcription factors. Post-cardiomyocyte formation p38γ/NKx2.5 downregulation is followed by p38α/MEF2c upregulation suggesting stage-specific developmental roles of p38 MAPK isoforms. Knockdown of p38γ MAPK similarly disrupts cardiomyocyte formation in spite of the presence of NKx2.5. Cell fractionation and NKx2.5 phosphorylation studies suggest inhibition of ErbB4-p38γ signaling hinders NKx2.5 nuclear translocation during early cardiogenesis. This study reveals a novel pathway that directly links ErbB4 and p38γ to the transcriptional machinery of NKx2.5-GATA4 complex which is critical for cardiomyocyte formation during mammalian heart development.